REACTION OF MOLECULAR OXYGEN WITH CHROMIUM, COBALT AND NICKEL METALLOCENES IN DIMETHYLSULFOXIDE. CORRELATION BETWEEN ITS POLAROGRAPHIC AND BOND LENGTHS PARAMETERS - Walter Zamudio; Nubia Duarte; Ana María García; Marcelo Campos Vallette (Journal of the Chilean Chemical Society, 2019)
The reaction of oxidation with molecular oxygen in dimethyl sulfoxide is of order one in the metallocenes; the specific reaction constant decreases from nickel, chromium to cobalt. A reaction mechanism is proposed. The values of the polarographic constants and the bond lengths vary linearly with respect to the increase of the specific reaction constant but with opposite slopes.